2021
DOI: 10.3390/genes12040519
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/2 Mutation Detection in the Tumor Tissue from Selected Polish Patients with Breast Cancer Using Next Generation Sequencing

Abstract: (1) Background: Although, in the mutated BRCA detected in the Polish population of patients with breast cancer, there is a large percentage of recurrent pathogenic variants, an increasing need for the assessment of rare BRCA1/2 variants using NGS can be observed. (2) Methods: We studied 75 selected patients with breast cancer (negative for the presence of 5 mutations tested in the Polish population in the prophylactic National Cancer Control Program). DNA extracted from the cancer tissue of these patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
1
10
0
1
Order By: Relevance
“…Sequencing was performed on a MiniSeq platform (Illumina) using the MiniSeq Mid Output Kit, 2 × 150 cycles, to obtain reads for both strands. Sequencing results were analyzed using EntroGen Variant Reporter v1.3 and Illumina Variant Studio 3.0 [ 11 ]. Single nucleotide variant (SNV) pathogenic alterations detected by NGS are listed in the supplementary data: Table S2 (see the electronic supplementary material).…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing was performed on a MiniSeq platform (Illumina) using the MiniSeq Mid Output Kit, 2 × 150 cycles, to obtain reads for both strands. Sequencing results were analyzed using EntroGen Variant Reporter v1.3 and Illumina Variant Studio 3.0 [ 11 ]. Single nucleotide variant (SNV) pathogenic alterations detected by NGS are listed in the supplementary data: Table S2 (see the electronic supplementary material).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to FANCD2 monoubiquitination which has a mild impact on HR, BRCA2 activity is essential for DNA double-strand break (DSB) repair ( 24 ). PALB2 and BRCA s genes have been well-reported due to their high prevalence in breast cancer where patients with PALB2 gene mutation were found to have shorter survival years ( 33 35 ). It was also reported that approximately 49.1% of thyroid cancer patients were found to have breast tumours ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic tests for BRCA1/2 genes are also a cost-efficient screening tool for patients with somatic or germline pathogenic variants who can benefit from PARP inhibitor (PARPi) therapy ( Forbes et al, 2019 ; McAlarnen et al, 2021 ; Szczerba et al, 2021 ; Yamamoto and Hirasawa 2021 ). Thus, BRCA1/2 sequencing is more and more commonly ordered by oncologists as a test performed on tDNA not only for patients with ovarian cancer but also for specific patients with prostate cancer and pancreatic cancer in whom such therapy could be considered ( McAlarnen et al, 2021 ; Szczerba et al, 2021 ). For such patients, a consultation with clinical geneticists still should be highly recommended and is crucial to determine whether the pathogenic variant is somatic or germline.…”
Section: Discussionmentioning
confidence: 99%